2000
DOI: 10.1046/j.1365-294x.2000.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation of Euterpe edulis Mart. populations estimated by AFLP analysis

Abstract: Heart-of-palm (Euterpe edulis Mart.) is a wild palm with a wide distribution throughout the Atlantic Rainforest. Populations of E. edulis represent important renewable natural resources but are currently under threat from predatory exploitation. Furthermore, because the species is indigenous to the Atlantic Rainforest, which is located in the most economically developed and populated region of Brazil, social and economic pressures have devastated heart-of-palm forests. In order to estimate the partitioning of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
54
1
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 36 publications
9
54
1
4
Order By: Relevance
“…The strong isolation by distance pattern found in this study is consistent with other large-scale studies of tropical trees, for example Caryocar brasiliense in the Cerrado area of Brazil (Collevatti et al 2001) and Euterpe edulis in the Brazilian Atlantic rainforest (Cardoso et al 2000). Isolation by distance was observed for Amazonian S. macrophylla (Lemes et al 2003), but the Mesoamerican populations also form natural groups based on geographical isolation, which raises the possibility that the pattern observed for Mesoamerican mahogany owes more to the geography of the region than distance per se.…”
Section: Genetic Differentiation Among Mesoamerican Populationssupporting
confidence: 92%
“…The strong isolation by distance pattern found in this study is consistent with other large-scale studies of tropical trees, for example Caryocar brasiliense in the Cerrado area of Brazil (Collevatti et al 2001) and Euterpe edulis in the Brazilian Atlantic rainforest (Cardoso et al 2000). Isolation by distance was observed for Amazonian S. macrophylla (Lemes et al 2003), but the Mesoamerican populations also form natural groups based on geographical isolation, which raises the possibility that the pattern observed for Mesoamerican mahogany owes more to the geography of the region than distance per se.…”
Section: Genetic Differentiation Among Mesoamerican Populationssupporting
confidence: 92%
“…When the four combinations were analyzed considering the sum of the loci of the four primer combinations, it was found that in Santa Luzia Buiçuzinho the polymorphism percentage was equal to the average polymorphism, while at the other sites these values varied little (Table 1). In studies on the palm species Euterpe edulis, Cardoso et al (2000) used five primer pairs and found 429 fragments of which 395 (92 %) were polymorphic. To evaluate the existence of three races of peach palm, a domesticated species, Clement et al (2002) used six primer combinations generating 245 fragments, of which 135 (55.1n%) were polymorphic.…”
Section: Resultsmentioning
confidence: 99%
“…This is the only Euterpe species in Brazil occurring outside the Amazon region, the center of origin of this genus of 30 species. It is a single‐stemmed, 5‐ to 15‐m‐tall palm, widely dispersed within the biome, between latitudes 15°S and 29°S (Cardoso, Eloy, Provan, Cardoso, & Ferreira, 2000). It was the most abundant species in the study areas of Rainforest and Restinga Forest, corresponding, respectively, to 19.8 percent and 21.5 percent of the stems with diameter at breast height >4,8 cm (Brancalion et al., 2012).…”
Section: Methodsmentioning
confidence: 99%
“…It was the most abundant species in the study areas of Rainforest and Restinga Forest, corresponding, respectively, to 19.8 percent and 21.5 percent of the stems with diameter at breast height >4,8 cm (Brancalion et al., 2012). Such widespread and abundant species is especially prone to geographic diversification, and molecular differentiation among E. edulis populations was found to be closely related to spatial proximity (Cardoso et al., 2000). Euterpe edulis has been considered a keystone species for frugivores in the Atlantic Forest, as it produces fruits that are consumed and dispersed by at least 30 bird and 15 terrestrial mammal and bat species.…”
Section: Methodsmentioning
confidence: 99%